2010
DOI: 10.1007/s11106-010-9229-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic treatment on the microstructure of NiAl–Re alloy

Abstract: The influence of the magnetic field on the dislocation structure of intermetallic NiAl-Re alloy is studied and is experimentally confirmed for the first time. Active displacement of dislocations is established. Rhenium inclusions perform stop functions in these conditions. In addition, Ni atoms move to the surface of the alloy and an Al-rich internal layer forms under the magnetic gradient. These results indicate that the new atomic configuration forms by diffusion due to jumps of Ni atoms to adjacent Ni vacan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…It was shown that the introduction of rhenium into NiAl alloys improved their mechanical properties [23]. Our previous study has showed that, as compared with Ni 64 Al 36 SMA, Ni 64 Al 34 Re 2 SMA can improve the alloy's hot workability and exhibits B2 ↔ L1 0 (3R) martensitic transformation with M s temperature at 365.8 K in asrolled condition [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the introduction of rhenium into NiAl alloys improved their mechanical properties [23]. Our previous study has showed that, as compared with Ni 64 Al 36 SMA, Ni 64 Al 34 Re 2 SMA can improve the alloy's hot workability and exhibits B2 ↔ L1 0 (3R) martensitic transformation with M s temperature at 365.8 K in asrolled condition [24].…”
Section: Introductionmentioning
confidence: 99%
“…We previously established that the microstructure and chemical composition of NiAl-Re alloy could vary under the magnetic field [1][2]. This is a promising effect for improving the properties of heat-resistant β-NiAl coatings, whose development is a very important area in aviation materials science.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of structural changes that occur in NiAl-Re alloy under the magnetic field was described previously [1,2]. Nickel atoms have uncompensated spin magnetic moment and can form microdomains with direct exchange interaction [11], which greatly intensifies the effect of the magnetic field applied [12].…”
Section: Introductionmentioning
confidence: 99%